Analisis Agihan Zakat oleh Penolong Amil Institusi Pengajian Tinggi di Selangor: Analysis of Zakat Distribution by Amil Assistants of Higher Education Institutions in Selangor - Md Ismail, Mohammad Noorazlan; Ali, Nor Aini (Online Journal of Research in Islamic Studies, 2022)
Lembaga Zakat Selangor (LZS) is the first Zakat institution to appoint institutions of higher education (IPT) as Amil assistants since 1998. This appointment enables students to receive Zakat assistance to cover part of their cost of study. Accordingly, this study discusses in detail the implementation of zakat distribution to students by the amil assistants of IPT. In this study, both documentation methods and interviews are used to collect research data. Two IPTs were selected as the sample for the study, namely Universiti Kebangsaan Malaysia (UKM) and Universiti Putra Malaysia (UPM). Then, the data were analyzed using content and thematic analysis methods. The results of the study show that zakat assistance was distributed by both IPTs to five categories of asnaf, namely fakir, miskin, fī sabīlillāh, mualaf and ibn sabīl. Zakat assistance is distributed in various forms, namely, financial assistance, assistance in equipment or study materials and development programs for asnaf. It has been shown that these aids can facilitate students’ study process and further increase their active participation in the university life. Future research proposals may explore the effectiveness of student support programs in aspects of academic performance, financial stability and engagement with the college.